Respuesta :

Answer:

a)  x = 1 is a solution

c)  x = -1 is also solution

Step-by-step explanation:

Explanation:-

Given rational equation

  [tex]\frac{4}{x+6} + \frac{1}{x^{2} } = \frac{x+10}{x^{2} (x+6)}[/tex]

Now  L.C.M  and simplification, we get

[tex]\frac{4x^{2} +X+6}{x^{2} (x+6)} = \frac{x+10}{x^{2}(x+6) }[/tex]

Now cancellation x²(x+6) on both sides, we get

4x²+x+6 = x +10

On simplification , we get

4x² +x+6 -x-10=0

4x²-4 =0

4(x²-1) =0

x²-1 =0

Apply Formula a²-b² = (a-b)(a + b)

(x-1)(x+1) =0

x =1 and x=-1

Hence x =1 and x =-1 is a solution of given rational function